Role of Kantor Urusan Agama (KUA) in the Control and Supervision of Product Halal-ness - Vionita Baros; Zaenal Abidin; Zeni Sunarti; Niskaromah (Zabags Qu Publish, 2025)
This study examines the role of the Kantor Urusan Agama (KUA) in controlling and supervising the halal status of products at the local level, using KUA Mendahara (Mendahara Ilir subdistrict) as a case study. Motivated by persistent implementation challenges in Indonesia’s Halal Product Assurance system, the research aims to clarify how KUA contributes to ensuring that halal certification follows regulatory requirements and how it monitors certified products in practice. Employing a qualitative case-study design, data were collected through in-depth interviews, direct field observation, and document analysis, and were analyzed thematically. Findings reveal four principal functions performed by KUA: disseminating information and conducting outreach on halal certification; providing technical guidance and administrative assistance to MSMEs during the certification process; coordinating cross-institutional activities with BPJPH, MUI, and local health authorities; and carrying out post-certification monitoring through field visits and administrative checks. The study demonstrates that KUA operates as a critical institutional intermediary between national policy and local practice. Theoretically, the research extends institutional perspectives to religious local institutions in halal governance; practically, it offers evidence-based recommendations to strengthen KUA capacity and interagency collaboration to improve the effectiveness and sustainability of Indonesia’s halal assurance system.